Every thing on it : poems and drawings - Silverstein, Shel. (New York : Harper, 2011)
A collection of more than 130 original, never-before published poems and drawings by Shel Silverstein.
School Library Journal starred, September 2011
Pub Weekly, July 2011
Booklist, September 2011
Horn Book, November 2011
Kirkus Review, August 2011
Includes index.
Keywords: Children's poetry, American; Humorous poetry; American poetry; Humorous poetry; American poetry; Humorous poetry